MANAJEMEN PROYEK PERANCANGAN SISTEM INFORMASI UNTUK PENJUALAN ALAT KESEHATAN - Asep Darmawan; Dedi Trisnawarman; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This research aims to ensure the successful completion of an information system design project for the sale of medical devices by CV Star Ayres Indonesia, a company involved in medical device distribution. Utilizing project management theories such as Work Breakdown Structure, Gantt Chart, Network Diagram, Critical Path Method, PERT Diagram, Risk Management, and Cost Management, the study focuses on identifying, planning, organizing, controlling, and evaluating the project. The analysis reveals that the project will take approximately 211 days, as determined by network diagram calculations using the Critical Path Method and PERT Diagram, considering potential risks. Additionally, the estimated cost for the project is Rp. 69,884,000, covering labor, transportation, hosting, printing, consumption, and other administrative expenses.